Cardiac cells and mesenchymal stem cells derived extracellular vesicles: a potential therapeutic strategy for myocardial infarction - Qin, Dan; Wang, Xiaobo; Pu, Jun; Hu, Houxiang (Frontiers in Cardiovascular Medicine, 2024)
Despite improvements in clinical outcomes of acute myocardial infarction (AMI), mortality rates remain high, indicating the need for further understanding of the pathogenesis and developing more effective cardiac protection strategies. Extracellular vesicles (EVs) carry proteins and noncoding RNAs (ncRNAs) derived from different cardiac cell populations, mainly including cardiomyocytes, endothelial cells, endothelial progenitor cells, cardiac progenitor cells, cardiosphere-derived cells, immune cells, fibroblasts and cardiac telocytes have vital roles under both physiological and pathological process such as myocardial infarction (MI). The content of EVs can also indicate the status of their parental cells and serve as a biomarker for monitoring the risk of cardiac injury. Examining these vesicles can offer fresh perspectives on the development of MI and assist in creating innovative treatments. Additionally, mesenchymal stem cells (MSCs) (MSC-EVs) derived EVs have been shown to have significant potential in cardiac regeneration. In this review, we will discuss the current understanding of the role of EVs in cardiac communication, with a focus on the perspectives of EVs from various cardiac cells and MSCs for their potential uses as cardiac therapies after MI.